Reasons for Treatment Noncompliance among Substance Abusers: An Outpatient Department-based Survey - Amanpreet Kaur; Sushil Kumar Maheshwari; Preksha Sharma (Indian Journal of Psychiatric Nursing)
Context: Psychoactive substance abuse in India continues to be spiral out of control, especially among Punjab. Linking drug users with the nearest de-addiction center is a herculean task, and treatment completion is a can of worms. Psychological characteristics of individuals, elements of their lifestyles, and treatment system factors may serve as barriers to successful linkage. Aims: The aim of the study is to assess reasons for treatment noncompliance and dropout among substance abusers who are visiting the tertiary-level outpatient department (OPD) of the department of psychiatry. Settings and Design: A quantitative research approach with a cross-sectional survey design was used for data collection from the OPD of a tertiary care hospital in Punjab, India. Materials and Methods: Data were collected to assess the reason for leaving treatment in 200 substance abusers who were selected conveniently using a sociodemographic sheet and the Reasons for Leaving Treatment Questionnaire-18. Statistical Analysis Used: Frequency distribution, mean, and t-test were used to compute results. Results: Majority (54.5%) of the substance users were using opioids. More than two-third (68.5%) of the subjects left the treatment incomplete, and only 31.5% of the subjects followed treatment properly. The mean of personal perspectives reasons (include few names) of leaving treatment was 20.39 ± 2.47, whereas the mean of program perspectives (include few names) reasons of leaving treatment was 14.26 ± 2.23. Conclusion: The study concluded that substance abusers left treatment due to personal perspectives reason rather than program perspective. Some interventional strategies should be planned to manage various reasons responsible for treatment dropout.